Mathematical optimization model of avionics complexation problem on early stage of designing - Vorobyov, V.M.; Belyh, T.V.; Zakharchenko, V.A.; Novikova, M.V.; Kondratenko, S.V. (Proceedings of National Aviation University (archive), 2006)
The article is the sequel of another one of this digest of authors “Approximate optimization solution by Pareto of discrete extremal problem of complexation of new generation avionics” and its development in the direction of creating optimization model and organization under synthesis of avionics structure.